To woo and to wed : a novel - Waters, Martha, 1988- (Waters, Martha, 1988- Regency vows series, 2024)
"West, the Marquess of Weston, and Sophie, Lady Fitzwilliam Bridewell, have lately been spending a considerable amount of time together. But West and Sophie are not new acquaintances. In fact, years ago, they had once been nearly engaged until West's almost fatal curricle accident and his meddling father threw them off course. Now, years later, Sophie and West are thrown back together as they conjure a plot to ensure Sophie's little sister gets to marry the love of her life. It'll be simple. After all, it's not like she is going to fall for West a second time, not when Sophie has sworn not to risk her heart again"--